2017
DOI: 10.1089/pho.2017.4343
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Exercise Infrared Photobiomodulation Therapy (810 nm) in Skeletal Muscle Performance and Postexercise Recovery in Humans: What Is the Optimal Power Output?

Abstract: PBMT with 100 mW power output per diode (500 mW total) before exercise achieves best outcomes in enhancing muscular performance and postexercise recovery. Another time it has been demonstrated that more power output is not necessarily better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 37 publications
6
64
2
6
Order By: Relevance
“…Three parallel lasers placed on the quadriceps femoris during treatment Journal of Human Kinetics -volume 73/2020 http://www.johk.pl Our results are inconsistent with other findings as de Oliveira et al (2017) showed that applying photobiomodulation (810 nm, energy of 300 J) before an eccentric protocol of knee extension increased maximal isometric voluntary contraction (MVC). This positive effect may be related to the higher energy delivered in their study.…”
Section: Figurecontrasting
confidence: 99%
“…Three parallel lasers placed on the quadriceps femoris during treatment Journal of Human Kinetics -volume 73/2020 http://www.johk.pl Our results are inconsistent with other findings as de Oliveira et al (2017) showed that applying photobiomodulation (810 nm, energy of 300 J) before an eccentric protocol of knee extension increased maximal isometric voluntary contraction (MVC). This positive effect may be related to the higher energy delivered in their study.…”
Section: Figurecontrasting
confidence: 99%
“…The first clinical trial in this field showed that PBMT before an exercise session could enhance the performance of high-level volleyball athletes (number of repetitions), decrease the delayed onset muscle fatigue (time until exhaustion), and prevent the expected increase of blood lactate levels [ 6 ]. After this pioneering clinical trial [ 6 ], PBMT used alone or in combination to static magnetic fields (sMF) have shown positive results in different kinds of exercises and protocols such as repeated contractions [ 6 , 7 ], isometric contractions [ 8 ], progressive-intensity running [ 9 11 ], cycling [ 12 , 13 ], eccentric contractions [ 14 17 ], strength training [ 18 , 19 ], endurance training in treadmill [ 20 ] and even in field tests [ 21 ]. Regarding exercise recovery, both PBMT and PBMT-sMF have shown better effects than other agents classically used for this aim, such as cryotherapy for instance [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that PBMT combined with sMF (PBMT-sMF) is able to promote ergogenic effects in a similar way to isolated PBMT [ 19 21 , 29 31 ]. Currently there is an increasing body of evidence for the use of both isolated PBMT and PBMT-sMF [ 32 , 33 ] with several aspects regarding the application of these therapies being elucidated, such as: optimal doses [ 12 , 13 , 15 , 16 ], optimal power output [ 17 ], and even comparisons between different devices commercially available [ 34 ]. However, the time-response window is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…The fibromyalgia case report suggests that the use of HILT at 42–75 W of power can produce more profound and longer-lasting beneficial effects than standard treatment protocols utilizing LLLT 79 and less powerful HILT devices 140 . Importantly, LLLT studies have reported that photobiomodulation therapy produced greater improvement in muscular performance and accelerating recovery when it is administered prior to exercising 143 , 144 . Although Foley et al 145 reported that LLLT facilitated a faster recovery of injured university athletes, they failed to include either a control or an active comparator group.…”
Section: Laser Therapymentioning
confidence: 99%
“…Finally, determining the optimal power and wavelength for each clinical condition is critically important in optimizing both LLLT and HILT. For example, de Oliveria et al 144 compared 100, 200, and 400 mW of power and found that with LLLT a higher power does not necessarily produce a better result with respect to improvement in muscle performance. These authors also recommended using a wavelength of 810 nm for achieving optimal results with LLLT.…”
Section: Laser Therapymentioning
confidence: 99%